The Impact of Workplace Bullying and Harassment on Employee Turnover in Banking Industry of Pakistan - RABIA INAM KHAN; MUHAMMAD NISAR KHAN; IHTESHAM KHAN (Journal of Business & Tourism, 2021)
This study has been executed with intent to find out the impact of workplace bullying and harassment on employees’ turnover among the bankers. Qualitative data was gathered through in-depth interviews from 50 bankers. Non- probability sampling technique was adopted. In this research study, the researcher has used the principle of purposive sampling. The results depict that bankers are being bullied but they do not want to leave their organizations due to bullying. There are many other factors that make them think to leave organization such as extreme stress, work burden and better opportunities for work. The results also revealed that employees who are being harassed do not disclose such incidents. This paper contains a message for the senior management of organizations to review their bullying and harassment policies. Moreover, this study suggests that there can be other factors that can be the reason for employee turnover.